Bare Singular Count Nouns in Dutch as a Heritage Language in Brazil / Nomes singulares nus em neerlandês como língua de herança (Revista de Estudos da Linguagem, 2019)
Abstract: The aim of this research was to evaluate the distribution of DPs in generic sentences, in Dutch Heritage Language Speakers (HLS) in Holambra, Brazil, especially regarding the acceptability of Bare Singular Count Nouns (BS). The Distribution of BS is more restricted in Dutch than in Brazilian Portuguese, nonetheless, we raised the hypothesis that, due to the influence of Brazilian Portuguese, these HLS would accept BS in contexts similar to those of Brazilians. We applied an acceptability judgement test to 60 adult HLS from Holambra (experimental group), 30 Brazilian monolinguals and 30 native Dutch speakers (control groups 1 and 2). We presented to each participant in the experimental group 10 Dutch stimulus sentences and 20 filler sentences in order to verify their acceptability on a five-item Likert scale. The results showed that sentences with BS eliciting a generic reading received high acceptability rates from the Experimental Group of Holambra (72% acceptability rate). These responses were more aligned with the Brazilian Control (78% acceptability rate) than with the Dutch Control (96% unacceptability rate). The statistical Regression Analysis of the BS showed that the Dutch Control had a significant divergent behavior (p.value =